Monetary Policy Environment and the Current Monetary Policy Framework in Nepal - Thapa, Nar Bahadur (Economic Journal of Nepal, 2011)
Monetary theories generally shape the framework of monetary policy. This paper briefly discusses the role of the Phillips Curve. Time Inconsistent Problem and the Real Business Cycle Theory in the evolution of the present framework of monetary policy at the global level. Following this, it delves into the operational framework in place in Nepal. In addition, the current issues relating to the operation of monetary policy in Nepal are also discussed with due consideration to the role of financial environment in the implementation of monetary policy.Key words: Monetary policy; Philips Curve; NepalEconomic Journal of Nepal A Quarterly Publication of the Central Department of Economics, Tribhuvan University, Kirtipur, KathmanduVol. 30, No.3, July-September, 2007Page :125-146Uploaded date: 21 July, 2011